Structural Credit Risk Models: A Review - Laajimi, Sadok (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2012)
In this paper, the author reviews the literature on credit structural models. Contingent claim analysis offers an appealing theoretical framework allowing not only evaluating firm’s claims and default risk, but also financing and investment decisions, as well as determining the impact of policy changes on the firm value and decisions. First, we present the major structural models and their underlying assumptions, beginning with exogenous default models and the following development leading to endogenous default models as well as other models that accounts for bankruptcy procedures, capital structure decisions and strategic defaults among others. The second part of the paper covers the empirical works related to the structural credit models. These works could be classified into three major categories: the first group examines the ability of structural models to explain the credit spread, the second one evaluate their performance to forecast default occurrence, the last group uses the structural models to study the relationship between credit risk and stock returns.